Pengaruh Konseling Kelompok Menggunakan Teknik Bibliokonseling Terhadap Kecakapan Sosial Siswa Di Smp Negeri 1 Timpeh - Egista Karningsih Deden Suhartono; Fadhilla Yusri; Muhiddinur Kamal; Syawaludin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Abstract This research is based on the phenomenon that exists in SMP Negeri 1 Timpeh, which shows that students are indicated to have low social skills, namely, it can be seen from the lack of courage of students to express opinions, work on questions in front of the class and ask teachers related to lesson materials and difficulties in controlling anger, students are less active during discussions, there are individualistic students, and group counseling services have not been implemented using bibliocounseling techniques to improve students' social skills, one of the guidance and counseling services is carried out, namely group counseling services using bibliocounseling techniques which aim to determine the effect of group counseling services using bibliocounseling techniques on students' social skills at SMP Negeri 1 Timpeh.This study uses a quantitative approach with the type of Pre Experiment Design, with the One Group Pretest and Posttest model. The population in this study amounted to 71 students in class VIII of SMP Negeri 1 Timpeh. The sampling technique in this study used purposive sampling, the sample of this study was 8 students. The instrument used in this study was a social skills questionnaire developed by the author. Data analysis in this study used the Wilcoxon renk test with the help of SPSS version 26. The results of the study processed using the Wilcoxon test showed that the Asymp sig 2-tailed value was obtained at 0.012 which means it is smaller than 0.05. So it can be concluded that group counseling services using bibliocounseling techniques have an effect on students' social skills at SMP N 1 Timpeh